Biogeographical zonation of rocky intertidal communities along the coast of Peru (3.5-13.5 degrees S Southeast Pacific) - Ibanez-Erquiaga, B (2018)
This work was funded by Concejo Nacional de Ciencias y Tecnología (CONCYTEC)—Peru. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript